Enhancing The Seventh Grade Students’ Vocabulary Mastery by Using Scrabble Game - Istigfariyanti, Safira Desita; T Andayani, Made Adi; Wahjuningsih, Eka (English Education Study Program, 2023)
Vocabulary as one of the English components cannot be separated from English skills. For EFL students, it is imperative to learn vocabulary first because vocabulary is related to all four skills. This research aimed to enhance the seventh-grade students’ vocabulary mastery by using scrabble game at MTs Sunan Ampel Banyuwangi. It was conducted by using Classroom Action Research (CAR) design with the four stages in a cycle model. The result showed that the percentage of students’ active participation improved from 76.47% in Meeting 1 to 85.29% in Meeting 2. It means that the students’ active participation in Cycle 1 achieved the criteria of success of this research. Meanwhile, the percentage of vocabulary test scores showed that the students who got score ≥75 increased from 73.5% in the previous score to 88.23% in the vocabulary score in Cycle 1. These results showed that the target of this research was achieved in Cycle 1, so it was not continued to Cycle 2. Based on the results of this research, it could be concluded that the use of scrabble game improved the students of the VII-A Class vocabulary mastery and active participation in the teaching and learning process of vocabulary at MTs Sunan Ampel Banyuwangi.